A new species of Diaphania H bner, 1818 from Ecuador (Lepidoptera: Crambidae: Spilomelinae) - Vila, Roger; Piñas, Francisco; Clavijo, José A. (Zootaxa, 2004)
Diaphania yurakyana n. sp. (Lepidoptera: Crambidae: Spilomelinae) is described from the tropical rainforest of Ecuador. This species is closely related to D. argealis (Walker, 1859), D. interpositalis (Hampson, 1912), and D. novicialis (Schaus, 1912). The female, immature stages, and larval hostplant are unknown.Se describe Diaphania yurakyana n. sp. (Lepidoptera: Crambidae: Spilomelinae) de la regi n tropical de Ecuador. Esta especie es cercana a D. argealis (Walker, 1859), D. interpositalis (Hampson, 1912) y D. novicialis (Schaus, 1912). La hembra, las fases inmaduras, y la planta nutricia de la larva son desconocidas.